Limits of flexibility – Case special collections, Tritonia, Finland - Rintamäki, Katri; Flemming, Christina; Toukonen, Jonna (Qualitative and Quantitative Methods in Libraries, 2019)
Academic libraries have many tasks in common with the universities, among others promoting lifelong learning, interacting with the surrounding society and promoting the social impact of university research findings. In this paper various strategies for how the third task can be implemented into the library activities in Tritonia, a joint academic library for five universities and universities of applied sciences in Vaasa, Finland, are discussed, based on the library’s special collections, above all from a collection point of view. The challenges for the academic libraries of the regions are many. Demands are made by outsiders on local preservation of the cultural heritage, prominent persons' private book collections, libraries of learned societies and others. The internal challenges in incorporation of new collections into the library are financing, the physical condition of the collections, lack of space, resources for cataloguing and handling of books. The library faces new demands concerning exhibition spaces and arranging attractive exhibitions. Digitalization and social media give new unforeseen opportunities, but require allocation of resources.